Coordination Between ROS Regulatory Systems and Other Pathways Under Heat Stress and Pathogen Attack - Suzuki, Nobuhiro; Katano, Kazuma (Frontiers in Plant Science, 2018)
Regulatory systems of reactive oxygen species (ROS) are known to be integrated with other pathways involving Ca2+ signaling, protein kinases, hormones and PCD pathways to regulate defense mechanisms in plants. Coordination between ROS regulatory systems and other pathways needs to be flexibly modulated to finely tune the mechanisms underlying responses of different types of tissues to heat stress, biotic stresses and their combinations during different growth stages. Especially, modulation of the delicate balance between ROS-scavenging and producing systems in reproductive tissues could be essential, because ROS-dependent programmed cell death is required for the proper fertilization, despite the necessity of ROS scavenging to prevent the damage on cells under heat stress and biotic stresses. In this review, we will update the recent findings associated with coordination between multiple pathways under heat stress, pathogen attack and their combinations. In addition, possible integrations between different signals function in different tissues via ROS-dependent long-distance signals will be proposed.